2017
DOI: 10.5603/nmr.a2016.0041
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of shortened gated myocardial perfusion imaging processed with „Myovation Evolution” with full time study

Abstract: BACKGROUND:The work compares the results of shortened gated myocardial perfusion imaging (MPI), processed with "Myovation Evolution" software, with a study performed in a standard way.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…Interestingly, no relationship between occurrence of those defects and patient obesity expressed in terms of a body mass index was found. The same trend (lower indices of diagnostic efficacy obtained for a shortened study) although less noticeable, could be observed in our previous work presenting results of interpretation of studies of the same patients but using different, segmental method [5]. Attenuation correction reduced differences between indices of diagnostic efficacy of full time and half time studies considerably.…”
Section: Originalsupporting
confidence: 59%
See 4 more Smart Citations
“…Interestingly, no relationship between occurrence of those defects and patient obesity expressed in terms of a body mass index was found. The same trend (lower indices of diagnostic efficacy obtained for a shortened study) although less noticeable, could be observed in our previous work presenting results of interpretation of studies of the same patients but using different, segmental method [5]. Attenuation correction reduced differences between indices of diagnostic efficacy of full time and half time studies considerably.…”
Section: Originalsupporting
confidence: 59%
“…They obtained agreement between full time and half time studies equal to 95% without AC and 96% with AC [6], 96% with 100% agreement in a clinical interpretation [7], and 83% to 96% (in case of acceptance of minor inconsistencies) [8]. A more detailed analysis of results presented in specified above publications was provided in our previous publication [5].…”
Section: Originalmentioning
confidence: 92%
See 3 more Smart Citations